Simple Foot Elevator for Diabetic Ulcer Treatment (SIFOEDT) - Majid, Abdul; Prayogi, Agus Sarwo; Surantono, Surantono; Hendarsih, Sri (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
a